The Utilization of Water Hyacinth for Biogas Production in a Plug Flow Anaerobic Digester - Soeprijanto, Soeprijanto; Warmadewanthi, I Dewa Ayu Agung; Muntini, Melania Suweni; Anzip, Arino (International Journal of Renewable Energy Development, 2021)
Water hyacinth (Eichhornia crassipes) causes ecological and economic problems because it grows very fast and quickly consumes nutrients and oxygen in water bodies, affecting both the flora and fauna; besides, it can form blockages in the waterways, hindering fishing and boat use. However, this plant contains bioactive compounds that can be used to produce biofuels. This study investigated the effect of various substrates as feedstock for biogas production. A 125-l plug-flow anaerobic digester was utilized and the hydraulic retention time was 14 days; cow dung was inoculated into water hyacinth at a 2:1 mass ratio over 7 days. The maximum biogas yield, achieved using a mixture of natural water hyacinth and water (NWH-W), was 0.398 l/g volatile solids (VS). The cow dung/water (CD-W), hydrothermally pretreated water hyacinth/digestate, and hydrothermally pretreated water hyacinth/water (TWH-W) mixtures reached biogas yields of 0.239, 0.2198, and 0.115 l/g VS, respectively. The NWH-W composition was 70.57% CH4, 12.26% CO2, 1.32% H2S, and 0.65% NH3. The modified Gompertz kinetic model provided data satisfactorily compatible with the experimental one to determine the biogas production from various substrates. TWH-W and NWH-W achieved, respectively, the shortest and (6.561 days) and the longest (7.281 days) lag phase, the lowest (0.133 (l/g VS)/day) and the highest (0.446 (l/g VS)/day) biogas production rate, and the maximum and (15.719 l/g VS) and minimum (4.454 l/g VS) biogas yield potential.